Mujeres en espacios étnicos: Relaciones prácticas, roles y estrategias (cacicazgos de Tarata, Tacna y Codpa, 1759-1803) - Inostroza Ponce, Xochitl (2023)
Drawing on the conceptualization of ethnic spaces, this article aims to characterize the daily life of women who inhabited the chiefdoms of Tarata, Tacna, and Codpa. The history of two mestizo women belonging to local chieftain families and that of the enslaved women owned by each of these women, is explored based on the wills of the former. Their situation is compared with that of two native women inhabitants of Belen town and two slaves of a priest who lived in the same doctrine, whose lives were reconstructed on the basis of parish books. Highlighting dissimilar aspects of their practical relationships allows for the differentiation of ethnic spaces.